Bioconjugation of Small Molecules to RNA Impedes Its Recognition by Toll-Like Receptor 7 - Hellmuth, Isabell; Freund, Isabel; Schlöder, Janine; Seidu-Larry, Salifu; Thüring, Kathrin; Slama, Kaouthar; Langhanki, Jens; Kaloyanova, Stefka; Eigenbrod, Tatjana; Krumb, Matthias; Röhm, Sandra; Peneva, Kalina; et al. (Frontiers in Immunology, 2017)
A fundamental mechanism of the innate immune system is the recognition, via extra- and intracellular pattern recognition receptors, of pathogen-associated molecular patterns. A prominent example is represented by foreign nucleic acids, triggering the activation of several signaling pathways. Among these, the endosomal toll-like receptor 7 (TLR7) is known to be activated by single stranded RNA (ssRNA), which can be specifically influenced through elements of sequence structure and posttranscriptional modifications. Furthermore, small molecules TLR7 agonists (smTLRa) are applied as boosting adjuvants in vaccination processes. In this context, covalent conjugations between adjuvant and vaccines have been reported to exhibit synergistic effects. Here, we describe a concept to chemically combine three therapeutic functions in one RNA bioconjugate. This consists in the simultaneous TLR7 stimulation by ssRNA and smTLRa as well as the therapeutic function of the RNA itself, e.g. as a vaccinating or knockdown agent. We have hence synthesized bioconjugates of mRNA and siRNA containing covalently attached smTLRa, and tested their function in TLR7 stimulation. Strikingly, the bioconjugates displayed decreased rather than synergistically increased stimulation. The decrease was distinct from the antagonistic action of an siRNA bearing a Gm motive, as observed by direct comparison of the effects in the presence of otherwise stimulatory RNA. In summary, these investigations showed that TRL7 activation can be impeded by bioconjugation of small molecules to RNA.